Czech Republic : Technical Note on Crisis Management and Bank Resolution Framework. (IMF Staff Country Reports; Country Report, 2012)
The Czech financial system is confronted with mounting risks that stem mainly from negative developments in the European Union (EU). This technical note focuses on crisis management and bank resolution framework for the Czech Republic. It summarizes the high-level observations of the mission based on its key findings and recommendations, and analyzes the existing institutional framework and coordination arrangements for crisis management. The note also examines the cross-border dimension of crisis preparedness and crisis management tools.